COMUNICAÇÃO (I)MATERIAL COM AS DIVINDADES – TIPOS E FORMAS DE EX-VOTOS NA RELIGIOSIDADE POPULAR - GORDO, LUIS ERLIN GOMES (2018)
This study aims to further our understanding of exvotos as a journalistic media and means of communication, updating both the concept and the typology. To this purpose, the general objective of the research is to study and update the typology of exvotos developed by Jorge González (researcher) and adopted by experts on Folk Communication, expanding the understanding of this phenomenon in the communication process related to religions, thus offering new possibilities for academic research in this field. The thesis was based on the hypothesis that the current classification of ex-votos adopted by researchers on Folk Communication needs updating, as the dynamics of this communication process, like others, is continually changing. Being millenary, the practice itself does not change, but its forms of expressions and contents (typology) do. In this sense, this phenomenon must be understood beyond Catholicism (which consolidated it), through the studies of its manifestations in other segments of Christianity and in various religions. For the development of this research, Folk Communication was taken as the theoretical framework, based on the studies developed by González, Luiz Beltrão and José Marques de Melo. The methodology consisted of bibliographical research and inventory method, which have already been applied in Folk Communication research related to ex-votos. The result of this study is the understanding of the exvoto phenomenon one step ahead of the conventional (Catholicism). Another contribution is the updating of the typology that has directed the studies on Folk Communication over the last decades, considering the dynamics of the human communication process.